2023
DOI: 10.1126/sciadv.adf8106
|View full text |Cite
|
Sign up to set email alerts
|

Yield-stress transition in suspensions of deformable droplets

Abstract: Yield-stress materials, which require a sufficiently large forcing to flow, are currently ill-understood theoretically. To gain insight into their yielding transition, we study numerically the rheology of a suspension of deformable droplets in 2D. We show that the suspension displays yield-stress behavior, with droplets remaining motionless below a critical body-force. In this phase, droplets jam to form an amorphous structure, whereas they order in the flowing phase. Yielding is linked to a percolation transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…These authors showed that, by suppressing cell overlap and increasing the duration of collisions, phase separation was facilitated by deformability. Deformability has also been shown to be important in the analysis of the rheology of a droplet suspension 28 .…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that, by suppressing cell overlap and increasing the duration of collisions, phase separation was facilitated by deformability. Deformability has also been shown to be important in the analysis of the rheology of a droplet suspension 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamics of the multiple droplets (i.e., translocation [61], coalescence, and permeation [62]) in microchannels are usually related to many engineering applications, i.e., cell migration, chemical mini-reactions, and porous materials. In addition, lab-on-chip microfluidic devices may be key components of high-performance computers (HPCs).…”
Section: Discussionmentioning
confidence: 99%
“…These materials transition from a solid-like state below a critical yield stress to a liquid-like state above it, a behavior pivotal to the functionality of diverse substances ranging from construction materials to personal care products ( 1 , 2 ). This transitional behavior arises from the microstructure interactions like jamming and attractive forces of colloids and gels ( 3 , 4 ), extending even to larger scales in geological and extraterrestrial contexts ( 5–7 ). The inherent elasticity of EVP fluids extends beyond their solid state, shaping their flow characteristics, enabling energy storage, and recovery postdeformation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%